Targeting cells of the myeloid lineage attenuates pain and disease progression in a prostate model of bone cancer. Issue 9 (September 2015) - Thompson, Michelle L.; Jimenez-Andrade, Juan M.; Chartier, Stephane; Tsai, James; Burton, Elizabeth A.; Habets, Gaston; Lin, Paul S.; West, Brian L.; Mantyh, Patrick W.
Abstract : Abstract: Tumor cells frequently metastasize to bone where they can generate cancer-induced bone pain (CIBP) that can be difficult to fully control using available therapies. Here, we explored whether PLX3397, a high-affinity small molecular antagonist that binds to and inhibits phosphorylation of colony-stimulating factor-1 receptor, the tyrosine-protein kinase c-Kit, and the FMS-like tyrosine kinase 3, can reduce CIBP. These 3 targets all regulate the proliferation and function of a subset of the myeloid cells including macrophages, osteoclasts, and mast cells. Preliminary experiments show that PLX3397 attenuated inflammatory pain after formalin injection into the hind paw of the rat. As there is an inflammatory component in CIBP, involving macrophages and osteoclasts, the effect of PLX3397 was explored in a prostate model of CIBP where skeletal pain, cancer cell proliferation, tumor metastasis, and bone remodeling could be monitored in the same animal. Administration of PLX3397 was initiated on day 14 after prostate cancer cell injection when the tumor was well established, and tumor-induced bone remodeling was first evident. Over the next 6 weeks, sustained administration of PLX3397 attenuated CIBP behaviors by approximately 50% and was equally efficacious in reducing tumor cell growth, formation of new tumor colonies in bone, and pathological tumor-induced bone remodeling. Developing a better understanding of potential effects that analgesic therapies have on the tumor itself may allow the development of therapies that not only better control the pain but also positively impact disease progression and overall survival in patients with bone cancer. Abstract : Supplemental Digital Content is Available in the Text.Inhibition of myeloid lineage attenuates bone cancer pain and disease progression.